1976
DOI: 10.1017/s0022172400055698
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of salmonellas from sewage-polluted river water using selenite F and Muller–Kauffmann tetrathionate

Abstract: SUMMARYSelenite F broth and a modified Muller-Kauffmann tetrathionate broth were investigated using sewage-polluted natural water as inocula. The modification of the tetrathionate medium was necessary as commercial alternatives would not allow multiplication of small numbers of salmonellas.The wide range of molar concentrations in different tetrathionate broths was emphasized.Selenite F broth was more efficient than Muller-Kauffmann tetrathionate broth, in our hands, with the material tested. Direct inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…In absolute numbers of salmonella isolations from pig faeces selenite F broth is more efficient than tetrathionate broth (P < 0.01) (of. (Harvey & Price, 1976). A similar bias fas also been published for S. dublin (Harvey & Price, 1975).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In absolute numbers of salmonella isolations from pig faeces selenite F broth is more efficient than tetrathionate broth (P < 0.01) (of. (Harvey & Price, 1976). A similar bias fas also been published for S. dublin (Harvey & Price, 1975).…”
Section: Discussionsupporting
confidence: 72%
“…We have made the point previously that using two complementary enrichment broths is better than using only one (Harvey & Price, 1976). Table 7 demonstrates the very wide variety of serotypes isolated from pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these circumstances we would prefer selenite and/or tetrathionate which can accept large amounts of potentially infected material. The use of two enrichment media has certain advantages as each may have a bias towards isolation of certain serotypes (Harvey & Price, 1976). In the current series of observations recorded in Table 4, no useful comment on serotype bias can be made.…”
Section: Resultsmentioning
confidence: 99%
“…There is also the theoretical possibility that certain serotypes may be recovered more easily from one of the enrichment media rather than from another. We have demonstrated this with sewage polluted water (Harvey & Price, 1976). Koopman & Janssen (1973), however, in a study of reptile faeces found no definite preference for an enrichment method by certain serotypes.…”
Section: C3mentioning
confidence: 78%